Analisis Perilaku Konsumsi Tepung Terigu Oleh Rumahtangga Peserta Program Keluarga Hadapan Di Kota Pekanbaru - Reffi Devani; Djaimi Bakce; Jumatri Yusri (Jurnal Pertanian Khairun, 2025)
Wheat flour is one of the main carbohydrate sources widely consumed by the community, including low-income households that are beneficiaries of the Family Hope Program (PKH). However, the increase in wheat flour prices and limited income affect the ability of PKH household participants to access and consume wheat flour. This study aims to analyze the factors influencing wheat flour consumption among PKH household participants in Pekanbaru City. The research employs a quantitative approach, conducted in Pekanbaru City with a total sample of 315 respondents. The sample was determined using a multistage sampling method with a simple random sampling technique. Data were analyzed using multiple linear regression and demand elasticity models. The results show that the prices of wheat flour, rice flour, glutinous rice flour, sago flour, granulated sugar, coconut sugar, chicken eggs, and cooking oil, as well as household size and income, significantly affect wheat flour consumption. Wheat flour consumption is elastic with respect to its own price but inelastic with respect to income, household size, and the prices of substitute goods such as rice flour, glutinous rice flour, sago flour, granulated sugar, coconut sugar, chicken eggs, and cooking oil. Therefore, the price of wheat flour itself is the most influential factor affecting its consumption among PKH households in Pekanbaru City. Thus, price control policies are essential to enhance the purchasing power of PKH households toward wheat flour